Redescription of the adults and new descriptions of the previously unknown immature stages of Culex (Culex) articularis Philippi, 1865 (Diptera: Culicidae) from central Chile - González, Christian R.; Reyes, Carolina; Rada, Viviana (Zootaxa, 2015)
Male and female adults of Culex (Culex) articularis Philippi are redescribed, and the 4th-instar larva and pupa are described and illustrated for the first time. Culex articularis is compared with other species of the subgenus Culex. Illustrations of diagnostic characters of the female, male genitalia, 4th-instar larva, and pupa are also provided.